فعالية الجباية المحلية في تمويل التنمية بقطاع البلديات، عرض حالة بلدية النخلة - عبابه, علي; شويرفات, عبد القادر (جامعة الوادي - University of Eloued, 2020)
ن الحديث عن التنمية في قطاع البلديات وعلى المستوى المحلي عموما يقودنا الى الحديث عن الامكانيات المتوافرة لدى الجماعات المحلية بصفة عامة والتي تمكنها من القيام بهذه المهام وابرازها للعلن، وهذا لا يكون الا بالوقوف على امكانياتها المادية ومصادر تمويلها، للتعريف تأتي هذه الدراسة للاطلاع على مصادر التمويل الجبائية للجماعات المحلية ولتوضيح فعاليتها في تمويل البلديات خصوصا مع الاسقاط على احد البلديات كعينة للتوضيح على سبيل الحصر لا التعميم لنعرف من خلالها معوقات تغطية الجباية المحلية لنفقات البلديات والتنمية بها، مع اقتراح بعض الحلول التي من شأنها ان تسهم في الرفع من حصيلتها وتغطية احتياجاتها من التمويل. The discussions on development in the community sector and at the local level in general lead us to talk about the possibilities offered to local communities in general, which allow them to carry out these tasks and to highlight them to the public. It is not only to identify their financial means and their sources of financing. And to clarify their efficiency in the financing of municipalities, in particular with the projection on one of the municipalities as a sample, it is necessary to clarify exclusively so as not to circulate through we know the obstacles of the local collection of municipal expenses and development, with the suggestion of solutions They help raise funds and cover their financing needs.
The effectiveness of local collection in financing development in the municipal sectorView the status of commune Nakhla
مقال
Keywords: الجباية المحلية ; البلديات ; التمويل المحلي ; الاصلاح الجبائي